The Physical Characterisation of Coating via Electrophoretic Deposition (EPD) with Voltage and Duration Variables for Solid Oxide Fuel Cell Application - A Review - Sharkawi, Nur Aishah; Azmi, Mohd Azham; Jaidi, Zolhafizi; Abd. Rahman, Hamimah; Ahmad, Sufizar; Mahzan, Shahruddin; Ismail, Azzura; Tajul Arifin, Ahmad Mubarak; Zakaria, Hanis; Hassan, Suhaimi (Journal of Advanced Mechanical Engineering Applications, 2021)
This review covers the basics of electrophoretic deposition techniques and its effect on the physical characterisation for solid oxide fuel cell application. On top of that, the characterisation of coating often affected by the variation of voltage. The higher the voltage, the more deposition weight obtained. The duration of deposition also crucial as it can influence the thickness of the coating layer. The thickness and morphology of the coating layer were determined by using scanning electron microscopy (SEM). For its weight deposited, there were several techniques has been applied.